THE TEACHING OF BRAZILIAN SIGN LANGUAGE (LIBRAS) IN PSYCHOLOGY COURSES IN BAHIA:: GAPS AND THEIR EFFECTS ON CLINICAL PRACTICE (PRÁXIS EM SAÚDE, 2025)
The history of the Deaf population is marked by numerous processes of exclusion. The late recognition of Brazilian Sign Language (Libras) as a language and its low dissemination in educational settings reflect this segregation. Access to health services, including mental health, is still limited for Deaf individuals, due to a lack of preparedness for their care. The roots of this issue begin with the training of professionals. This study aims to investigate the inclusion of the Libras discipline in Psychology courses at universities in the state of Bahia and to explore how its presence—or absence—impacts clinical practice. The research, which is exploratory, descriptive, and documentary, reveals that the inclusion of Libras in Psychology courses predominantly appears as an elective subject with a low workload, limited to superficial teaching disconnected from clinical practice. The results show that this gap produces professionals incapable of properly serving Deaf individuals. A curricular reform is urgently needed to ensure accessible psychological practice, without the sovereign prevalence of monolingualism.
Keywords: Deafness; Brazilian Sign Language (Libras); Psychology; Training